2006
DOI: 10.1177/1934578x0600100104
|View full text |Cite
|
Sign up to set email alerts
|

Lignans from the Stem of Cinnamomum camphora

Abstract: Diasesamin (1), (+)-sesamin (2), (+)-episesamin, stearic acid, palmitic acid, a mixture of β-sitosterol and stigmasterol, and a mixture of β-sitosterol-D-glucoside and stigmasterol-D-glucoside were isolated from the stems of Cinnamomum camphora (L.) Presl.. Among these compounds, 1 is obtained for the first time from a natural source. The cytotoxicity of 2 on Hep G2 and HeLa cell cancer lines was also investigated. The flow cytometric assay results indicated that 2 elicited a decrease in the percentage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…dealbata shows a statistically significant cytotoxic activity on the lung cancer cell line NCI-H292 with an IC 50 of 1 g/L compared to non-cytotoxic activity against a normal lung epithelial cell line (Figure 1 A-B). These results agree with previously reported anti-cancer properties of sesamin extracted from other sources [7][8][9][10]16] and the protective effect of sesamin on normal neuronal and PC12 cells [10].…”
supporting
confidence: 93%
“…dealbata shows a statistically significant cytotoxic activity on the lung cancer cell line NCI-H292 with an IC 50 of 1 g/L compared to non-cytotoxic activity against a normal lung epithelial cell line (Figure 1 A-B). These results agree with previously reported anti-cancer properties of sesamin extracted from other sources [7][8][9][10]16] and the protective effect of sesamin on normal neuronal and PC12 cells [10].…”
supporting
confidence: 93%
“…However, at the concentration of 25 µg/mL, sesamin was reported to inhibit the growth of brain, lung, and breast cancer cell lines (Mulabagal et al ., ). In addition, this compound induced autophagy in the human HT29 and LS180 colon cancer cell lines (Tanabe et al ., ) and inhibited the DNA synthetic event in HepG2 cells (Hsieh et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Mixture of 17 and 18 (121 mg) were recrystallized from fraction 5 (7.8 g) to afford crystals. Known compounds were characterized by comparison of their spectroscopic data with literature values [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Extraction and Separationmentioning
confidence: 99%
“…In the previous studies, its stem wood was found to contain four butanolides, one secobutanolide, four flavonoids, three flavans, two lignans, eight benzenoids, six steroids, one triterpenoid, one diterpenoid, two furans and nine aliphatic compounds from this species [1]. As part of our continuing investigation of the phytochemical and bioactive compounds of Formosan Lauraceous plants [2,3], a new butanolide, kotomolide (1), together with 17 known compounds, obtusilactone A (2) [4], isoobtusilactone A (3) [4], secokotomolide (4) [1], kaempferol (5) [5], quercetin (6) [6], (-)-catechin (7) [7], (-)-epicatechin (8) [8], (-)-sesamin (9) [9], isoeugenol (10) [10], trans-ferulic acid (11) [11], benzoic acid (12) [12], p-hydroxybenzoic acid (13) [13], p-hydroxybenzaldehyde (14) [13], a mixture of β-sitosterol (15) and stigmasterol (16) [14], and a mixture of β-sitosterol-D-glucoside (17) and stigmasterol-D-glucoside (18) [15], were obtained via chromatographic fractionation of the methanolic extract of the stems of this plant. Known compounds 2, 8, 10 and 13 were also isolated for the first time from this species.…”
mentioning
confidence: 99%